Ethnic and national identity in Bosnia-Herzegovina - Doubt, Keith. (Lanham)
ix, 106 sayfa
Keywords: “In Ethnic and National Identity in Bosnia-Hersegovina, Keith Doubt and Adnan Tufekčić analyze Bosnian social organization, cultural character, and boundary maintenance. Doubt and Tufekčić argue that Bosnians live in a polyethnic society, defined by a set of marriage and kinship practices that cross ethnic and national identity divisions. This book provides readers with a clearer understanding of Bosnian identity and the role of ethnic groups in an increasingly complex society.“ --